DAYA TERIMA ES KRIM BIKACMER KACANG MERAH (Phaseolus vulgaris L) DENGAN PENAMBAHAN VARIASI BUAH BIT (Beta vulgaris L) - Nasution, Erlina; Sri Heriyanto; Iin (Poltekkes Kemenkes Medan, 2026)
Ice cream is a frozen food product created by emulsifying dairy products or a mixture of milk, with or without the addition of other food ingredients, and pasteurized with or without air incorporation.This study aimed to determine the acceptability of red bean (Phaseolus vulgaris L) 'Bikacmer' ice cream with varying additions of beetroot (Beta vulgaris L). This was an experimental study using a completely randomized design with 3 treatments and 2 replications.Organoleptic tests were conducted by 50 semi-trained panelists. The treatments in this study involved adding 30 gr red beans with 25 gr beetroot (Treatment A), 30 gr red beans with 50 gr beetroot (Treatment B), and 30 gr red beans with 75 gr beetroot (Treatment C).